GAYA BAHASA DALAM NOVEL SANDIWARA BUMI KARYA TAUFIQURRAHMAN AL-AZIZY - Zuniarti, Elni; Priyadi, Antonius Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstrak: Penelitian ini bertujuan untuk mendeskripsikan gaya bahasa dalam novel Sandiwara Bumi karya Taufiqurrahman Al-Azizy. Metode penelitian yang digunakan adalah deskriptif artinya data yang diperoleh dianalisis dan diuraikan menggunakan kata-kata ataupun kalimat bukan dalam bentuk angka-angka atau menggunakan perhitungan. Hasil analisis data menghasilkan kesimpulan, pertama; Gaya bahasa perbandingan yang meliputi majas antonomasia berjumlah 5 buah, hiperbola berjumlah 22 buah, metafora berjumlah 3 buah, personifikasi berjumlah 4 buah, simile berjumlah 14 buah. Kedua, Gaya bahasa pertentangan yang meliputi majas antitesis berjumlah 3 buah, kontradiksio berjumlah 10 buah; dan prolepsis/antisipasi berjumlah 1 buah. Ketiga, Gaya bahasa sindiran yang meliputu majas ironi berjumlah 2 buah; dan inuendo 2 buah. Keempat, Gaya bahasa perulangan yang meliputi majas alonim berjumlah 4 buah, asindeton berjumlah 10 buah, pizeukis berjumlah 27 buah, epanalepsis berjumlah 1 buah, polisindeton berjumlah 7 buah, klimaks berjumlah 10 buah; dan zeugma berjumlah 5 buah. Kata Kunci: Gaya Bahasa, Novel Â Abstract: This study aimed to describe the style languague in the novel Sandiwara Bumi Al-Azizy Taufiqurrahman work. The method used is descriptive meaning that the data obtained were analyzed and described using words or phrases not in the form of numbers or use calculations. Results of the data analysis resulted in the conclusion, first; a style that includes the figure of speech antonomasia ratio amounted to 5 pieces, hyperbole totaling 22 pieces, totaling 3 pieces metaphor, personification consists of 4 pieces, simile amounted to 14 pieces. Secondly, the language style that includes the figure of speech antithetical opposition amounted to 3 pieces, kontradiksio totaling 10 pieces, prolepsis/anticipation numbered 1 pieces. Third, the language style of satire which includes irony figure of speech amounted to 2 pieces;Â and inuendo amounted to 2 pieces. Fourth, the language style looping covering alonim figure of speech amounted to 4 pieces, asyndeton totaling 10 pieces, epizeukis totaling 27 pieces, numbered 1 pieces epanalepsis, polisindeton amounted to 7 pieces, 10 pieces totaling climax, and zeugma amounted to 5 pieces. Keyword: Style language, Novel